Neuroanatomical markers of neurological soft signs in recent-onset schizophrenia and asperger-syndrome - Hirjak, Dusan; Paternoga, Isa; Kubera, Katharina Maria; Thomann, Anne K.; Thomann, Philipp (Brain topography, 2016)
Neurological soft signs (NSS) are frequently found in psychiatric disorders of significant neurodevelopmental origin. Previous MRI studies in schizophrenia have shown that NSS are associated with abnormal cortical, thalamic and cerebellar structure and function. So far, however, no neuroimaging studies investigated brain correlates of NSS in individuals with Asperger-Syndrome (AS) and the question whether the two disorders exhibit common or disease-specific cortical correlates of NSS remains unresolved. High-resolution MRI data at 3 T were obtained from 48 demographically matched individuals (16 schizophrenia patients, 16 subjects with AS and 16 healthy individuals). The surface-based analysis via Freesurfer enabled calculation of cortical thickness, area and folding (local gyrification index, LGI). NSS were examined on the Heidelberg Scale and related to cortical measures. In schizophrenia, higher NSS were associated with reduced cortical thickness and LGI in fronto-temporo-parietal brain areas. In AS, higher NSS were associated with increased frontotemporal cortical thickness. This study lends further support to the hypothesis that disorder-specific mechanisms contribute to NSS expression in schizophrenia and AS. Pointing towards dissociable neural patterns may help deconstruct the complex processes underlying NSS in these neurodevelopmental disorders.